Regulation of cyclooxygenase-2 (COX-2) expression in human pancreatic carcinoma cells by the insulin-like growth factor-I receptor (IGF-IR) system - Stoeltzing, Oliver (2007)
Both the insulin-like growth factor-I receptor (IGF-IR) and cyclooxygenase-2 (COX-2) are frequently overexpressed in pancreatic cancer. We hypothesized that IGF-IR is directly involved in induction of COX-2 and sought to investigate signaling pathways mediating this effect. Pancreatic cancer cells (L3.6pl) were stably transfected with a dominant-negative receptor (IGF-IR DN) construct or empty vector (pcDNA). Cells were stimulated with IGF-I to determine activated signaling intermediates and induction of COX-2. Signaling pathways mediating COX-2 induction were identified using signaling inhibitors. IGF-I up-regulated COX-2 selectively via the MAPK/(Erk1/2) pathway. In addition, IGF-IR DN cells showed a marked decrease in constitutive COX-2 and a blunted response to IGF-I. Similarly, treatment with an anti-IGF-IR antibody effectively inhibited IGF-IR and MAPK/Erk activation and decreased COX-2 in parental cells. In conclusion, activation of IGF-IR mediates COX-2 expression in human pancreatic cancer cells.